Intramuscular loading dose of quinine for falciparum malaria: pharmacokinetics and toxicity. - Wattanagoon, Y; Phillips, R; Warrell, D; Silamut, K; Looareesuwan, S; Nagachinta, B; Back, D (1986)
In a study of intramuscular injection of quinine eight adults with moderately severe falciparum malaria resistant to chloroquine were treated with quinine dihydrochloride, being given a loading dose of 20 mg salt (16.7 mg base)/kg followed by three or four eight hourly maintenance doses of 10 mg salt (8.3 mg base)/kg injected into the anterior thigh. All patients responded to treatment. Fever and parasite clearance times (mean (SD) 60 (23) h and 53 (22) h respectively) were comparable with those obtained with intravenous quinine. The mean peak plasma quinine concentration of 11.0 mg/l (34.4 mu mol/l) [corrected] was reached a median of five hours after administration of the loading dose. In all patients plasma quinine concentrations exceeded the high minimum inhibitory concentration for Plasmodium falciparum malaria prevalent in Thailand within four hours of the start of treatment but did not cause toxicity other than mild cinchonism. When intravenous infusion is not possible an intramuscular quinine loading dose is an effective means of starting treatment in patients with moderately severe falciparum malaria who cannot swallow tablets.